Guidelines for authors-English Version - NA, NA (Universidad Santo Tomás / Instituto Colombiano de Normas Técnicas y Certificación ICONTEC, 2014)
Journal SIGNOS “Investigación en sistemas de gestión” aims to serve as a means of dissemination for reflections, discussions and findings on issues related to quality, quality management, various models of standardized management and social responsibility. This journal also aims to give space to experiences related to the applicability, innovation and relevance of theories, as well as management systems applicability in private and public organizations.